Parking Space Detection Using Computer Vision: A Systematic Review of the Literature - Mario CONDE-IBARRA; Brain RICSE-GÚRGURA; Javier GAMBOA-CRUZADO; Segundo TÁVARA-APONTE; Anibal SIFUENTES-DAMIÁN; Rosa MENENDEZ-MUERAS; Isaac SÁNCHEZ-CÁCERES (Communications of International Proceedings, 2021)
Currently, the business environment, which every company faces, is highly competitive and changing. Today’s innovation is tomorrow's standard and this is no different in parking lots, which also face a very competitive environment. It involves various factors that determine the level of demand, such as the use of technologies that can automatically detect free space, which would exponentially enhance this process by giving it a competitive advantage. In this study, a systematic literature review (SLR) was conducted to identify studies in the most relevant information sources for science, mapping them, critically evaluating the quality criteria, discarding studies by exclusion criteria, consolidating them, and compiling the results of relevant studies regarding the mentioned topic. The results presented in this article show the most used terms in the titles and abstracts of computer vision studies, the solutions that exist within computer vision, the most productive years in the application areas that employ this science, and complementary research topics.
Keywords: Parking; Machine Vision; Free Space Detection; Systematic Literature Review